Pemberdayaan Perempuan Melalui Pelatihan Video Marketing “Reels Instagram” Guna Meningkatkan Penjualan Produk Fashion di Desa Kemitir, Kabupaten Semarang - Setya Indah Isnawati; Rina Purwanti; Ulfamiyati Ulfamiyati; Prajna Paramita (Compromise Journal Community Proffesional Service Journal, 2024)
Video marketing strategy plays a very big role in efforts to reach potential customers and campaigns for a brand which will have an impact on increasing product sales. One of the online business people with the greatest interest is women. This is because women have free time to run their business 24 hours a day, as well as business communication skills that can easily influence potential customers. However, on the other hand, the acceleration of technology means that most, if not all, business people must be able to keep up. The most important factor is skills in managing marketing content which is the main media in online business. Women are actually connoted as a gender that is less skilled in technology and is forced to master marketing content. Therefore, this community service activity is intended to provide a solution in the form of training in creating marketing video content to improve marketing so that it has an impact on increasing product sales. The method used is in the form of direct assistance and training in making marketing videos, with the target object being women business actors and non-business actors, who are members of the Kemitir Village PKK. The results and outcomes of this service activity are the creation of new skills for women in Kemitir Village in making short videos which are uploaded to Instagram reels as marketing content.